THE EFFECT OF ALCOHOLIC EXTRACT Eriobotrya japonica LEAVES ON SOME BACTERIAL GENES AND SOME CHEMICAL AND MICROBIOLOGICAL PROPERTIES OF BEEF - & et al., Alwash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to investigate the effect of using alcoholic extract of yangadnia leaves on some bacterial strain Salmonella typhimiurum, E.coli  and  staphylococcus aures  in 200, 100, 50 and 25 mg/ml concentration using digging method. Minced cow meat 200 mg/ml   was mixed with yangdina extract and stored for 0,2,4 day at 4 C and tested for chemical and biological characteristics. The ruselts showed that the best concetration of inhibition was 200mg/ml and the inhibition zone diameters were 26, 19, 15 mm for S. aures, S. typhimiurm    and E .coli  respectively. In respect to Effect of extract in minced cow the ruselts showed drop in  values of, thiobarbituric acid (TBA),total violate nitrogen (TVN), total number account of bactria and count of psycrotrophic bactria and effect on PH values. It can be concluded that  yangdina leaves extract has inhibitory effect on bacterial strain and best concetration  200mg/ml. Mixing  meat with extract improved the storage life at 4c for 4 day.